E-commerce transactions in a virtual environment: virtual transactions - Scarle, S.; Arnab, S.; Dunwell, I.; Petridis, P.; Protopsaltis, A.; de Freitas, Sara (Springer, 2012)
E-commerce is a fundamental method of doing business, such that for a firm to say it is trading at all in the modern market-place it must have some element of on-line presence. Coupled with this is the explosion of the “population” of Massively Multiplayer On-line Role Playing Games and other shared virtual environments. Many suggest this will lead to a further dimension of commerce: virtual commerce. We discuss here the issues, current roadblocks and present state of an e-commerce transaction carried out completely within a virtual environment; a virtual transaction. Although technically such transactions are in a sense trivial, they raise many other issues in complex ways thus making V-transactions a highly interesting cross-disciplinary issue. We also discuss the social, ethical and regulatory implications for the virtual communities in these environments of such v-transactions, how their implementation affects the nature and management of a virtual environment, and how they represent a fundamental merging of the real and virtual worlds for the purpose of commerce. We highlight the minimal set of features a v-transaction capable virtual environment requires and suggest a model of how in the medium term they could be carried out via a methodology we call click-through, and that the developers of such environments will need to take on the multi-modal behavior of their users, as well as elements of the economic and political sciences in order to fully realize the commercial potential of the v-transaction.